Comparative study on physiological response characteristics of white clover to chloride salt and calcium‐magnesium acetate (CMA) deicing agents under freeze–thaw stress. (3rd October 2019) - Bian, Wenjie; Bao, Guozhang; Liao, Jiafen; Zhang, Qian; Chen, Weiwei; Guan, Shimei; Zhu, Mengdan; Zhu, Saning; Li, Haiyi; Ding, Xuemei
Abstract: The application of deicing agents often coincides with freeze–thaw (FT); however, the physiological effects of the sodium chloride deicing agent and concentrated calcium‐magnesium acetate (CMA) deicing agent on plants in the FT environment are not well investigated. To explore the physiological response characteristics of white clover seedlings under different kinds of deicing agents and FT stress, the changes in the content of total soluble protein, soluble sugar, malondialdehyde (MDA), superoxide dismutase (SOD) and peroxidase (POD) of white clover seedlings were determined under the simulated stress of FT and deicing agent (DA). The results indicated that the soluble protein content in the white clover seedlings decreased, whereas the contents of MDA and soluble sugar, and the activities of SOD and POD increased under the FT stress. In the FT cycle, the content of soluble sugar under single FT stress, and the activities of SOD and POD of the three FT groups all showed a negative correlation with temperature. The MDA showed a significant correlation with other indicators, and the correlations among the other above physiological indexes were not significant ( p < 0.05). The combined stress of FT + DA can cause increased plant damage, such as lipid peroxidation and osmotic potential imbalance. As an environmentally friendly DA, concentrated CMA was less harmful to plants than sodium chloride DA, but still brought damage to plants inevitably. Our results and corresponding discussion highlight the new findings on the effects of two kinds of deicing agents on plants under FT stress.